Fresno Chapter of Women's International League for Peace and Freedom Celebrating Louise Erickson and Marcia McLane - Watkins, Howard::::::::: (1989)
Marcia McLane and Louise Erickson about to cut birthday cake "150 YEARS WITH THE RIGHT WOMEN Women's International League for Peace and Freedom"